Addendum: de Souza Mesquita, L.M., et al. Modulatory Effect of Polyphenolic Compounds from the Mangrove Tree Rhizophora mangle L. on Non-Alcoholic Fatty Liver Disease and Insulin Resistance in High-Fat Diet Obese Mice. Molecules, 2018, 23, 2114 - Leonardo Mendes de Souza Mesquita; Cíntia Rabelo e Paiva Caria; Paola Souza Santos; Caio Cesar Ruy; Natalia da Silva Lima; Débora Kono Taketa Moreira; Claudia Quintino da Rocha; Daniella Carisa Murador; Veridiana Vera de Rosso; Alessandra Gambero; Wagner Vilegas (Molecules, 2019)
The authors wish to add the process number in the Acknowledgments section in this paper [...]